Veno-Venous Extracorporeal Membrane Oxygenation in Covid-19—Where Are We Now? - Zbigniew Putowski (International Journal of Environmental Research and Public Health, 2021)
The recent development in extracorporeal life support (ECLS) has created new therapeutic opportunities for critically ill patients. An interest in extracorporeal membrane oxygenation (ECMO), the pinnacle of ECLS techniques, has recently increased, as for the last decade, we have observed improvements in the survival of patients suffering from severe acute respiratory distress syndrome (ARDS) while on ECMO. Although there is a paucity of conclusive data from clinical research regarding extracorporeal oxygenation in COVID-19 patients, the pathophysiology of the disease makes veno-venous ECMO a promising option.